Bronchoalveolar lavage in occupational lung diseases - Robalo-Cordeiro, C (2007)
Occupational lung diseases (OLDs) are related to the exposure and inhalation of organic, inorganic, and synthetic particles, fumes, gases, or infectious agents. From the long list of OLDs this article focuses the discussion on bronchoalveolar lavage (BAL) in parenchymal immunoinflammatory conditions, such as hypersensitivity pneumonitis (HP) and pneumoconiosis. Several antigens may cause HP, including products of plant or animal origin, aerosolized microorganisms, and organic chemicals. BAL is used not only to assess the pathogenesis of these diseases but also to identify the typical pattern of intense lymphocytic alveolitis, usually with a CD4:CD8 ratio below normal and frequently with the presence of mast cells, plasma cells, and foamy macrophages. Pneumoconioses are chronic interstitial lung diseases caused by the inhalation of mineral and metallic inorganic particles/dusts in an occupational setting, showing a decreasing prevalence in recent years. BAL is a useful tool not only to express the complex pathogenic mechanisms of these entities but also in excluding other diagnoses and causes of alveolitis, and to document specific exposures, such as the identification of asbestos bodies (ABs) in asbestosis or the proliferative response of BAL lymphocytes to beryllium in chronic beryllium disease (CBD).